Lymphocyte proliferative response to Helicobacter pylori antigens in H. pylori-infected patients - Hybenová, Monika; Hrdá, Pavlína; Potužníková, Běla; Pavlík, Emil; Stejskal, Vera; Doseděl, Josef; Šterzl, Ivan (Folia microbiologica, 2010)
Helicobacter pylori (Hp) contributes to the development of gastric and extra-gastric diseases such as autoimmune thyroiditis (AT), and causes persistent life-long infection despite local and systemic immune response. We determined the specific cellular immune response to Hp antigens and PWM (control mitogen) in two groups of Hp infected patients--group A (n = 21), involving patients with autoimmune thyroiditis and group B (n = 13) of patients without AT--using modified lymphocyte transformation test before and after eradication therapy in comparison with healthy controls (group C, n = 15). Immune reactivity to the majority of Hp antigens (aHp, hHp, HpAg, CagA) was significantly lower in group B before eradication therapy in comparison with healthy Hp negative controls. A significant increase in immune reactivity was observed in group B to certain Hp antigens after successful eradication. The same levels (but insignificant) of immune reactivity were shown in group A. Our results indicate that Hp can cause the inhibition of the specific cellular immune response in Hp infected patients with or without autoimmune diseases such as AT, which can be abrogated by successful eradication of Hp. Lymphocyte transformation test appears to be a good tool for detection of immune memory cellular response in patients with Hp infection
Keywords: financování organizované; dospělí; Helicobacter; proliferace buněk; Female; antigeny bakteriální; lymfocyty; Adult; ženské pohlaví; Immune Tolerance; lidé; autoimunitní tyreoiditida; Thyroiditis, Autoimmune; Financing, Organized; Male; Cell Proliferation; Antigens, Bacterial; Lymphocytes; lidé středního věku; imunologická tolerance; mužské pohlaví; Helicobacter Infections; Middle Aged; infekce vyvolané Helicobacter pylori; Humans